1964
DOI: 10.1039/tf9646002196
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical production of alkyl and alkoxyl radicals and their reactions with oxygen

Abstract: The flash photolysis of a series of alkyl nitrites, halides and nitro compounds has been studied using the technique of kinetic spectroscopy in the vacuum ultra-violet region. During the flash photolysis of methyl nitrite, a new transient absorption spectrum consisting of three diffuse bands with centres at 2064, 2036, 1999A, was observed. The spectrum has been assigned to the CH30* radical, which must be produced in the initial photolytic breakdown according to h v CH30NO +CH30*+NO.Experiments using the highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1969
1969
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 6 publications
(9 reference statements)
1
8
0
Order By: Relevance
“…Merryman (1965a, 1967) applied the flame microstructure technique to derive the kinetics and mechanisms of some of the high temperature oxidation processes, while Bradley and Dobson (1967) studied the high temperature oxidation of H.S in shock waves. McGarvey and McGrath (1964), using the flash photolysis technique, and Marsden (1963), employing mass spectrometric techniques, have identified and further confirmed the presence of several intermediates in the H>S oxidation mechanism.…”
Section: His Oxidationmentioning
confidence: 78%
See 2 more Smart Citations
“…Merryman (1965a, 1967) applied the flame microstructure technique to derive the kinetics and mechanisms of some of the high temperature oxidation processes, while Bradley and Dobson (1967) studied the high temperature oxidation of H.S in shock waves. McGarvey and McGrath (1964), using the flash photolysis technique, and Marsden (1963), employing mass spectrometric techniques, have identified and further confirmed the presence of several intermediates in the H>S oxidation mechanism.…”
Section: His Oxidationmentioning
confidence: 78%
“…McGarvey and McGrath (1964), on the other hand, offer specific evidence for the SO radical in the photolytic oxidation of H2S. Using the flash-photolysis technique, they observe a spectrum for SO in the ultraviolet region of 2400 to 1900 Á.…”
Section: The Lower Sulfur Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The photochemistry of nitromethane (CH 3 NO 2 ) has been extensively studied for many years principally because the molecule is an important prototypical energetic material. Its ultraviolet absorption spectrum consists of two bands: a weak band around 270 nm with very little absorption strength at wavelengths longer than 350 nm and a very much stronger band at about 198 nm .…”
Section: Introductionmentioning
confidence: 99%
“…The minimum energy geometry is bent, but the existence of a low-lying SO 2 isomer was first suggested as an explanation for the strong continuous absorption band which resulted from flashinitiated explosions of H 2 S, CS 2 , and COS. [29][30][31] Assuming that the molecule responsible for the absorption band was a direct precursor to SO 2 , many investigated the possibility of a superoxide (S-O-O) isomer. 29,32,33 Influenced by the studies of Shih et al 8 on cyclic-O 3 , the possibility of a low-lying ring isomer of SO 2 began to be investigated. 23,[34][35][36][37] Kellogg et al found that all three SO 2 isomers were minima at the MRCI level of theory.…”
Section: Introductionmentioning
confidence: 99%